Sprawiedliwość jako wartość prawa prywatnego UE. W stronę wspólnego społeczeństwa? - Helios, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
In this article the author presents a problem of justice in EU private law. Although private law does not provide a comprehensive shape of distributive justice, it makes a crucial contribution. In the theoretical literature we do not encounter one definition of justice. This article contains the analysis of the definition of justice in the context of contract law and social model. In the author’s opinion a clear definition of justice is impossible in the context of traditional public/private divide. Generally this article focuses on the common identity in EU private law. So, one part of this paper is devoted to the problem of the European Civil Code. The European Union should develop a civil code to provide uniform rules for contract, property rights and protection against civil wrongs, thus drawing together the differing national traditions with respect to the detailed regulation of civil society.
Keywords: sprawiedliwość; prawo prywatne; Unia Europejska; wspólne społeczeństwo